Web-Based Attendance Information System At Diskominfosantik Bekasi District With Prototype Method - Panjaitan, John David Willy; Rifa'i, Anggi Muhammad; Suprianto, Asep (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
The rapid development of information technology has encouraged government agencies to utilize digital systems to improve operational efficiency and effectiveness, including in managing employee attendance data. This study aims to design and implement a Web-Based Attendance Information System at the Department of Communication, Informatics, Statistics, and Encryption (Diskominfosantik) of Bekasi Regency. The system was developed using the prototype method, allowing for a gradual design process involving users directly in evaluation and development. The main features of the system include login authentication for administrators and employees, barcode scanning for attendance validation, GPS data integration to verify attendance locations, digital leave requests, and real-time attendance data management and reporting. System testing was conducted using the black box testing method across various scenarios to ensure all functions operated as expected without errors. The system design is also supported by use case and class diagrams that illustrate the workflow and relationships between entities in the system. The results of the study indicate that the web-based attendance information system can improve recording accuracy, accelerate the attendance data recap process, and support transparency in personnel management. Thus, the system has the potential to serve as a model for other government agencies in digitizing employee attendance processes.